2001
DOI: 10.1034/j.1600-0501.2001.012001079.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone classification: an objective scale of bone density using the computerized tomography scan

Abstract: Dental implants are subject to masticatory loads of varying magnitude. Implant performance is closely related to load transmission at the bone-to-implant interface where bone quality will be highly variable. The type and architecture of bone is known to influence its load bearing capacity and it has been demonstrated that poorer quality bone is associated with higher failure rates. To date, bone classifications have only provided rough subjective methods for pre-operative assessment, which can prove unreliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
293
17
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(366 citation statements)
references
References 20 publications
20
293
17
13
Order By: Relevance
“…In our study, the recorded bone density values 330 ±49HU, which is slightly lower than the bone density reported in a study by Norton and Gamble 2001 [17]. They observed that the mean bone density values in the anterior mandible, the posterior mandible, the anterior maxilla and the posterior maxilla were 970 HU, 669 HU, 696 HU and 417 HU, respectively.…”
Section: Results and Findingscontrasting
confidence: 52%
See 1 more Smart Citation
“…In our study, the recorded bone density values 330 ±49HU, which is slightly lower than the bone density reported in a study by Norton and Gamble 2001 [17]. They observed that the mean bone density values in the anterior mandible, the posterior mandible, the anterior maxilla and the posterior maxilla were 970 HU, 669 HU, 696 HU and 417 HU, respectively.…”
Section: Results and Findingscontrasting
confidence: 52%
“…Hounsfield value for alveolar bone in the human jaw ranges from >0 and 850> Hounsfield [17,18]. The bone formation was consistent regardless of gender, age, age group or the diameter of the implant the graft was placed around.…”
Section: Results and Findingsmentioning
confidence: 88%
“…12 Several comparative studies confirmed the reliability and high accuracy of 3D CT for quantitative and qualitative analyses [13][14][15] and concluded that CT is a valuable diagnostic supplement to subjective bone density evaluation. [16][17][18] Cone beam computed tomography (CBCT) is preferred in dentistry as a result of the lower radiation dose it affords compared to that required in standard CT. However, standardization between CBCT machines is low, 7 which causes Hounsfield scale variability.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining of the CT based 3D virtual model of the craniofacial structures as well as the defect area has been reported as the preliminary requirements for the surgeon to select an appropriate site for patients whose anatomy does not allow placement of implants conventionally [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, implant locations can be planned virtually [26,28,29]. For this purpose, implant site may be scanned radiographically or optically [30][31][32] and modeled digitally [33][34][35]. Surgical guides produced with stereolithographic (STL) techniques in order to the computerized tomography (CT)-based planning, may be employed in surgical intervention [36][37][38].…”
Section: Introductionmentioning
confidence: 99%